Fil'm o khudozhnike Pitere Rubense . Fil'm o khudozhnike Pitere Rubense . Film About the Artist Peter Rubens . Фильм о художнике Питере Рубенсе - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Introduced by the artist and filmmaker Harold van de Perre. Contributors: Van de Perre, Harold (Director) Фильм представляет художник и автор фильма Харольд Ван де Перре. Создатели: Ван де Перре, Харольд (Режиссер)